Tinjauan Literatur tentang Kompetensi Profesional Guru Matematika - Aurelia Az Zahra; Nur Harun Ismail; Ikmawati Ikmawati; Achmad Muhtadin (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2026)
This study aims to examine in depth the professional competence of mathematics teachers through a literature review approach. The method used in this research is a literature review by analyzing ten relevant scientific articles obtained from various credible national and international sources. The study was conducted to identify the factors influencing the professional competence of mathematics teachers and its implications for the quality of learning and students’ learning outcomes. The findings reveal that mathematics teachers’ professional competence plays a significant role in improving the effectiveness of the learning process, students’ critical thinking skills, and mathematics learning achievement. Factors influencing professional competence include continuous training, academic supervision, teacher certification, teaching experience, intrinsic motivation, and the integration of digital technology in learning activities. In addition, professional competence is closely related to pedagogical competence in supporting students’ mathematical skills. The findings of this study emphasize that the development of mathematics teachers’ professionalism should be carried out systematically, continuously, and adaptively to technological advancements in order to improve the quality of mathematics education in the digital era.